The Modernizations of Capture Fisheries and Fishers’ Welfare Level in Pangandaran Regency. (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
Fisheries modernization in Indonesia is expected to improve productivity and strengthen the welfare of coastal communities. This study aimed to examine the relationship between the modernization of capture fisheries and fishers’ welfare in Pangandaran Regency. A survey of 60 fishers was conducted using snowball sampling, supported by in-depth interviews and a literature review. Modernization was measured through indicators such as capital, engine power, vessel size, and gear price, while welfare was assessed through income, expenditure, education, health, catch volume, and housing conditions. The analysis employed Spearman’s Rank correlation, complemented by qualitative evidence. The results indicated that most fishers remained at a low to medium level of modernization, while their welfare is generally in the medium category. A strong positive correlation was confirmed between modernization and welfare (ρ = 0.530; p < 0.01). These findings suggest that modernization contributes to better welfare, although the benefits are not distributed evenly, with vessel owners gaining more advantages than crew members. Policy implications highlight the importance of phased financing schemes, improved landing infrastructure, and better protection for small-scale fishers.